Effect of sowing dates and nitrogen management on thermal time requirement and heat use efficiency of Rabi maize in Odisha - DEEPIKA NALLI; SUPRAVA NATH; TUFLEUDDIN BISWAS (Journal of Agrometeorology)
Rapid climate changes are imperative and it is crucial to evaluate and find ways that work for nitrogen (N) fertilizer management with appropriate sowing dates to prevent critical growth stages from being impacted by changing climatic conditions. Considering this, a field experiment was carried out in the Rabi season of 2023-24 at the Post Graduate Research Farm of Centurion University of Technology and Management, Odisha. The experiment was laid out in a split-plot design with different sowing dates and nitrogen split applications at different times with varying proportions. The main plots consisted of four sowing dates and four nitrogen split applications were considered in sub-plots. Results revealed that the early sown crop (31st October) took a higher number of days and heat units to attain various phenophases. Maize sown on 31st October consumed maximum heat units of 1750 ℃ days and the significantly highest heat use efficiency (HUE) of 3.56 kg ha-1 ℃ day-1 for grain yield compared to minimum heat units (1665℃ days) and the significantly lowest HUE of 2.81 kg ha-1 ℃ day-1 for 15th December sown crops. Among split applications of nitrogen, treatment consisting of 25% N basal+25% N prior to knee high + 25% N at knee high +25% N at tasseling recorded the highest HUE (3.55 kg ha-1 ℃ day-1). The sowing of maize crop on 31st October with 25% N basal+25% N prior to knee high + 25% N at knee high +25% N at tasseling have been found to be the most efficient for heat utilisation.